Comparison of the effects of intra-articular Hyaluronic Acid Versus Methyl Prednisolone Acetate in Iraqi patients with Knee Osteoarthritis; A Double-Blind Controlled Study - Ibraheem, Mohammed J.; AL- Zobaidy, Mohammed AH.; AlTekreeti, Sami S. (Journal of the Faculty of Medicine Baghdad, 2025)
ABSTRACT : Background: Osteoarthritis is a prevalent chronic joint condition that occurs when the cartilage, which acts as a low-friction surface between the joints, deteriorates, resulting in pain, stiffness, and swelling. There has been controversy about the effectiveness and tolerability of corticosteroids and hyaluronic acid, and about the superiority of one over the other in treating OA. Objective current study aimed to compare the efficacy and safety of hyaluronic acid (HA) and methylprednisolone (MP) in the treatment of OA. Methods: One hundred and four patients with OA were randomized to receive intra-articular injection of either HA or MP, and they were followed for 3 months. Each patient from each group received a single injection at the time of enrollment. The participants and the evaluator were blinded to the nature of the injected material. The primary outcomes were to measure the change from baseline in Western Ontario McMaster University Osteoarthritis (WOMAC) index and visual analogue pain scale, and to record any treatment-related adverse events. Results: there were 49 females and 3 males in the HA group (mean age 59 ± 15.5) and 46 females and 6 males in the MP group (mean age 63 ± 15.5). Both groups demonstrated improvements in WOMAC and VAS scores throughout the follow-up period. The effect size for WOMAC and VAS scores favored HA over MP from month 2 to month 3 (P < 0.05). Both interventions were relatively safe, and no serious adverse events were reported. Conclusion: the results showed that both interventions are effective in relieving pain and improving knee stiffness and physical function. Furthermore, the current study showed that the most important difference between the two interventions is the duration of effectiveness. The benefit of HA was maintained to 3 months while that of MP declined after 1 month.